(untitled) (Journal of Hama University, 2022)
The Aim Of The Current Research Is To Reveal The Differences In Psychological Needs Between Normal Individuals And War Injuries, And To Identify The Relative Importance Of Psychological Needs And Their Dimensions According To The Answers Of The Sample Members. Through The Application Of The Psychological Needs Scale Prepared By The Researcher On A Sample Of (124),(88) Of Them Are Normal And (36) Are Physically Injured Due To The War, Their Ages Ranged Between (22-50) Years. The Researcher Used The Descriptive Analytical Method To Get The Results That Showed That There Are No Differences In The Scores Of The Sample Members On The Psychological Needs Scale Or One Of Its Dimensions, And The Relative Importance Of Psychological Needs And Their Dimensions For Normal And Injured Individuals Were, Respectively: The Need For Leadership, Then The Need For Recognition And Consideration, Followed By The Need To Structure Time, And Finally The Need For Stimulation And Excitement. The Researcher Recommended Making Use Of The Leadership Skills Of War Injuries, Which Appear In The High Satisfaction Of The Need For Leadership.